Effects of supplementation with phosphorus, calcium and manganese during oil palm frond fermentation by Phanerochaete chrysosporium on ligninase enzyme activity - Roni Pazla; Novirman Jamarun; Fauzia Agustin; Mardiati Zain; Arief Arief; Nesya Oktiacahyani (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Pazla R, Jamarun N, Agustin F, Zain M, Cahyani NO. 2020. Effects of supplementation with phosphorus, calcium and manganese during oil palm frond fermentation by Phanerochaete chrysosporium on ligninase enzyme activity. Biodiversitas 21: 1833-1838. The objective of this study was to evaluate the effects of supplementation with phosphorus (P) in combination with calcium (Ca) and manganese (Mn) during oil palm frond (OPF) fermentation by Phanerochaete chrysosporium on ligninase enzyme activity and lignin degradation. This study was carried out using a randomized complete design with 3 treatments (addition of P, Ca and Mn) and 5 replicates. The following treatments were performed: T1 (P 1000 + Ca 2000 + Mn 150 ppm), T2 (P 1500 + Ca 2000 + Mn 150 ppm), and T3  (P 2000 + Ca 2000 +Mn 150 ppm). The data were subjected to an analysis of variance (ANOVA), and differences between treatment means were tested using Duncan's multiple range test (DMRT). The parameters measured were as follows: lignin peroxidase (LiP) activity (U/mL), manganese peroxidase (MnP) activity (U/mL), crude protein (CP) content (%), crude fiber (CF) content (%) and the decrease in lignin (%). The results revealed a significant increase in LiP activity and CP content and a decrease in the lignin content (p<0.05) by the addition of P in the T3 treatment. However, the treatment nonsignificantly increased (p>0.05) MnP activity and significantly decreased (P<0.05) the CF content. In conclusion, supplementation of the OPF fermentation process with P 2000, Ca 2000, and Mn 150 ppm resulted in the highest ligninase enzyme activity and in decreased lignin content.